Method for ultraviolet resistant finishing of super-thin polyamide fabric
Patent Information
- Application Number
- CN202611284582.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-16
AI Technical Summary
但锦纶本身抗紫外性能较差,无法有效抵御紫外线对人体皮肤的伤害
1、本发明采用溶胶制备、复配整理液调制与连续浸轧整理一体化工艺,将二氧化钛溶胶、受阻胺型光稳定剂与三元紫外吸收剂组合物等助剂的添加、负载与锦纶织物整理集成于同一整理工作液中完成,无需分阶段操作,工艺实施简单,可利用现有的染色加工处理设备,大幅简化生产流程,降低生产工时与人力成本,便于规模化生产。本发明选用超薄锦纶织物,以二氧化钛溶胶作为无机紫外散射组分、以三元复配紫外吸收剂作为有机紫外吸收组分、以受阻胺型光稳定剂作为自由基捕获组分,三者在同一整理工作液中复配相容。经整理后的织物抗紫外性能显著提升,且具有优良的耐水洗耐久性。
Smart Images

Figure CN122918831A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of functional textile finishing, specifically relating to a method for UV-resistant finishing of ultra-thin nylon fabrics. Background Technology
[0002] With the ongoing global ozone hole problem and growing public awareness of health, the damage caused by ultraviolet radiation to human skin (such as sunburn, photoaging, and even skin cancer) is receiving increasing attention. Nylon fabrics, with their lightweight, high strength, quick-drying properties, and excellent elasticity, have become a core material for summer sun-protective clothing, skin-friendly garments, and outdoor sports equipment. However, nylon itself has poor UV resistance and cannot effectively protect human skin from UV damage. Imparting superior and long-lasting UV protection to nylon fabrics is a core industry requirement, especially for ultra-thin nylon fabrics, whose structural characteristics significantly increase the difficulty of UV protection.
[0003] Currently, the preparation methods for UV-resistant nylon fabrics are mainly divided into two categories: one is to add UV-resistant agents during the spinning stage. Although this can achieve long-term retention of UV resistance, the process is complex and costly, and the UV-resistant agents are unevenly dispersed, making it impossible to guarantee a uniform protective effect. It can also easily lead to embrittlement of nylon fibers. The other is post-treatment modification, which is the mainstream method in the industry. However, existing post-treatment methods mostly adopt multi-step methods, requiring the loading of UV-resistant agents, light stabilizers, and other auxiliaries in different steps. The core drawback is that the UV-resistant agents are unevenly loaded and have poor compatibility, making it difficult to achieve a stable UPF 50+ UV resistance effect. In addition, the washability is poor, and the UV resistance decreases sharply after multiple washes. At the same time, multiple finishing processes can easily damage the soft hand feel of nylon fabrics.
[0004] In addition, using nano-TiO2 particles directly as UV stabilizers can easily lead to agglomeration, affecting the uniformity of UV protection. Organic UV stabilizers, when used alone, have poor light resistance, are easily degraded, and have a short UV protection duration. Even when the two are combined, they still need to be operated in steps, making it impossible to balance high-efficiency UV protection performance with the soft feel of nylon fabrics. Summary of the Invention
[0005] This invention addresses the shortcomings of existing technologies by providing a method for UV-resistant finishing of ultra-thin nylon fabrics and the resulting ultra-thin UV-resistant nylon fabrics. This invention improves the UV resistance of ultra-thin nylon fabrics by compounding titanium dioxide sol with a specific composition of UV absorbers, hindered amine light stabilizers, and other auxiliaries in the same finishing working solution and employing a continuous pad-on finishing process.
[0006] To solve the above-mentioned technical problems, the objective of this invention is achieved through the following technical solution: A method for UV-resistant finishing of ultra-thin nylon fabric, comprising: Titanium dioxide sol, hindered amine light stabilizer, UV absorber composition, dyeing accelerator, inorganic UV stabilizer and crosslinking agent are dispersed in an aqueous medium and the pH is adjusted to 4-6 to prepare a homogeneous finishing working solution. The weight is 50±2 g / m 2 The nylon fabric is placed into the finishing working solution for continuous padding finishing, the continuous padding finishing including at least one immersion and at least one rolling, the roll-off rate is controlled to be 40% to 70%, so that the finishing working solution is evenly loaded on the surface and inside of the fabric fibers. The fabric loaded with finishing solution was pre-baked and then baked at high temperature to obtain an ultra-thin UV-resistant nylon fabric. The ultraviolet absorber composition comprises the commercially available compound ultraviolet absorber UV-3640, hexyl diethylaminohydroxybenzoylbenzoate, and 2-(benzo[d]thiazol-2-yl)-4-chlorophenol.
[0007] As a further improvement of the present invention, the continuous dip-roll finishing is a two-dip two-roll process, which includes: performing one dip and one roll in sequence, and then repeating one dip and one roll.
[0008] As a further improvement of the present invention, the mass parts of each component in the ultraviolet absorber composition, based on the mass of nylon fabric, are as follows: 0.2 to 0.5 parts of commercial compound ultraviolet absorber UV-3640, 0.05 to 0.15 parts of diethylaminohydroxybenzoylhexyl benzoate, and 0.02 to 0.06 parts of 2-(benzo[d]thiazolyl)-4-chlorophenol.
[0009] As a further improvement of the present invention, the finishing working solution includes a compound solution for impregnation and a rolling solution; The compound solution for impregnation, based on the weight of the nylon fabric, comprises the following components by mass: hindered amine light stabilizer 0.02–0.2 parts, UV absorber composition 0.25–0.70 parts, aqueous medium 30–60 parts, dyeing accelerator 0.05–0.15 parts, inorganic UV-resistant auxiliary agent 0.04–0.2 parts, and crosslinking agent 0.3–0.6 parts. In the rolling solution, based on the mass of the aqueous medium, the mass parts of each component are as follows: 0.03 parts hindered amine light stabilizer, 0.14 parts ultraviolet absorber composition, 0.02 parts dyeing accelerator, 0.002 parts inorganic anti-ultraviolet auxiliary agent, and 0.01 parts crosslinking agent.
[0010] As a further improvement of the present invention, the preparation method of the titanium dioxide sol includes: mixing tetrabutyl titanate and ethanol, adding glacial acetic acid to adjust the pH to 4-5, stirring, and then adding a mixture of deionized water and ethanol dropwise, stirring continuously for 3-4 h, and then allowing it to stand and age at 25-35°C for 12-24 h to obtain the titanium dioxide sol; wherein, the mass ratio of tetrabutyl titanate to ethanol is 1:5-55, and the mass ratio of tetrabutyl titanate to deionized water is 1:2-3.
[0011] As a further improvement of the present invention, the aqueous medium of the finishing working solution is a mixture of titanium dioxide sol and deionized water, and the mass ratio of titanium dioxide sol to deionized water is 1:1 to 4; the hindered amine light stabilizer is UV-660 or UV-770; and the crosslinking agent is a capped polyurethane crosslinking agent or a multifunctional aziridine crosslinking agent.
[0012] As a further improvement of the present invention, during the impregnation process, the finishing working solution is heated to 50-55°C and then added to the nylon fabric, and the temperature is increased to 85-95°C at a rate of 1.0-1.5°C / min and held for 30-70 min; the rolling treatment is carried out at room temperature.
[0013] As a further improvement of the present invention, the pre-baking temperature is 70-100℃ and the pre-baking time is 2-5 min; the high-temperature baking temperature is 120-160℃ and the baking time is 1-2 min.
[0014] As a further improvement of the present invention, the ultra-thin UV-resistant nylon fabric has a UPF value ≥ 2900, and the average transmittance of UVA and UVB is less than 3%.
[0015] The present invention also provides an ultra-thin UV-resistant nylon fabric prepared by the above method, wherein the average UVA transmittance and average UVB transmittance of the fabric are both less than 5% after 10 standard household washes.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention employs an integrated process of sol preparation, compound finishing solution formulation, and continuous pad-dip finishing. The addition and loading of auxiliaries, including titanium dioxide sol, hindered amine light stabilizer, and a ternary UV absorber composition, are completed within the same finishing working solution, eliminating the need for staged operations. The process is simple to implement, can utilize existing dyeing and processing equipment, significantly simplifies the production process, reduces production time and labor costs, and facilitates large-scale production. This invention uses ultra-thin nylon fabric, employing titanium dioxide sol as the inorganic UV scattering component, a ternary compound UV absorber as the organic UV absorbing component, and a hindered amine light stabilizer as the free radical capturing component. All three components are compounded and compatible within the same finishing working solution. The finished fabric exhibits significantly improved UV resistance and excellent wash resistance and durability.
[0017] 2. Compared to using the commercially available compound UV absorber UV-3640 alone, the introduction of diethylaminohydroxybenzoyl hexyl benzoate effectively fills the protection gap in the long-wave UVA band. 2-(benzo[d]thiazol-2-yl)-4-chlorophenol has a smaller molecular weight and better penetration into nylon fibers than macromolecular UV absorbers, allowing it to enter the fiber interior and provide protection. The flexible long-chain structure of diethylaminohydroxybenzoyl hexyl benzoate improves the hand feel of nylon fabrics. The above three UV absorbers exhibit good compatibility and stability in the finishing solution, significantly improving the full-band UV protection performance of the finished fabric.
[0018] 3. This invention uses the sol-gel method to prepare titanium dioxide sol. Compared with the direct addition of nano TiO2 particles, sol-state titanium dioxide has a smaller agglomeration particle size and better dispersion stability in aqueous media. After processing, it can be evenly distributed on the fiber surface and has a stronger bond with the fiber.
[0019] 4. The ultra-thin nylon fabric treated by this invention exhibits a uniform and continuous film formation on its surface, without any stiffness in the hand or color change, thus preserving the original softness and breathability of the nylon fabric. Furthermore, this invention is applicable to both ultra-thin undyed nylon fabrics and dyed nylon fabrics, demonstrating good process adaptability and practical application value. Attached Figure Description
[0020] Figure 1 The values are the ultraviolet transmittance of various embodiments of the present invention, wherein (a) is Embodiment 1, (b) is Embodiment 2, (c) is Embodiment 3, (d) is Embodiment 4, (e) is Embodiment 5, and (f) is Embodiment 6; Figure 2 This refers to the ultraviolet transmittance of Example 1 and the original fabric. Wherein (a) represents Example 1 and (b) represents the original fabric; Figure 3 This is the UV protection performance test record of Example 1. Detailed Implementation
[0021] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0022] In the following embodiments of the present invention, the ultraviolet protection factor (UPF) and UVA / UVB transmittance of the fabrics were measured according to the standard GB / T 18830-2009 "Evaluation of Ultraviolet Protection Performance of Textiles".
[0023] Example 1 1. Preparation of titanium dioxide sol Tetrabutyl titanate was added to ethanol, and glacial acetic acid was added to adjust the solution to acidity. The solution was then mechanically stirred until homogeneous to obtain solution a. Deionized water was added to ethanol and stirred until homogeneous to obtain solution b. Solution b was slowly added dropwise to solution a (the purpose of slow addition is to prevent rapid hydrolysis of the titanium source). After the addition was completed, mechanical stirring was continued for 3.5 hours. After stirring was stopped, the solution was allowed to stand at room temperature of 25°C for 18 hours to obtain a uniformly dispersed titanium dioxide sol.
[0024] The mass ratio of tetrabutyl titanate to ethanol was 1:10; the mass ratio of tetrabutyl titanate to fabric was 1:1; glacial acetic acid was used to adjust the pH of the solution to 4; the stirring rod was used at a speed of 300 r / min for 30 min. The required mass ratio of deionized water to tetrabutyl titanate was 2.5:1, and the mass ratio of ethanol to deionized water was 2:1.
[0025] 2. Preparation of the compound solution for impregnation Titanium dioxide sol and deionized water were mixed at a mass ratio of 1:1 as the base solvent (i.e., aqueous medium). Hindered amine light stabilizer, UV absorber composition, dyeing accelerator, inorganic UV stabilizer, and crosslinking agent were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5. The mixture was mechanically stirred for 3.5 hours to obtain a homogeneous and stable impregnation compound solution.
[0026] The base solvent to fabric water bath ratio is 30:1 (i.e., 30 parts of aqueous medium); the hindered amine light stabilizer is UV-660, with a dosage of 0.08 parts (i.e., 8% of fabric weight) based on the weight of the nylon fabric; in the UV absorber composition, UV-3640 is 0.27 parts, DHHB is 0.06 parts, and 2-(benzo[d]thiazol-2-yl)-4-chlorophenol is 0.03 parts (i.e., 27%, 6%, and 3% of fabric weight, respectively); the dyeing accelerators are sodium sulfate and micron-sized silica, with dosages of 0.2% (i.e., 0.002 parts relative to the aqueous medium) based on the weight of the aqueous medium, which is equivalent to 0.06 parts based on fabric weight; the inorganic UV-resistant auxiliary agent is nano-zinc oxide particles (particle size 30±10 mm). nm), based on the fabric weight, is 0.075 parts (i.e., 7.5% of the fabric weight); the crosslinking agent is a water-soluble end-capped polyurethane crosslinking agent, based on the water medium weight, is 1% (i.e., 0.01 parts), which is equivalent to 0.30 parts based on the fabric weight.
[0027] 3. Prepare the rolling fluid Titanium dioxide sol and deionized water were mixed at a mass ratio of 1:1 as the base solvent (i.e., aqueous medium). Hindered amine light stabilizers, UV absorber compositions, dyeing accelerators, inorganic UV stabilizers, and crosslinking agents were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5. The mixture was continuously mechanically stirred for 3.5 hours to obtain a homogeneous and stable rolling solution.
[0028] Based on the mass of the aqueous medium: hindered amine light stabilizer UV-660 is 0.03 parts (i.e., 3% of the mass of the aqueous medium); in the UV absorber composition, UV-3640 is 0.10 parts, DHHB is 0.03 parts, 2-(benzo[d]thiazol-2-yl)-4-chlorophenol is 0.01 parts; dyeing accelerator (sodium sulfate and micron-sized silica) is 0.02 parts; inorganic UV-resistant auxiliary agent (nano zinc oxide particles with a particle size of 30±10 nm) is 0.002 parts; crosslinking agent (water-soluble end-capped polyurethane crosslinking agent) is 0.01 parts.
[0029] 4. Fabric finishing Nylon fabric (weight 50±2 g / m) 2 The nylon fabric is immersed in a compound solution for impregnation. The initial water bath temperature is 50℃, and the temperature is increased to 90℃ at a rate of 1.0~1.5℃ / min, and held for 35 minutes to complete the first impregnation. The wetted fabric is then placed in the above padding solution and padded at room temperature and 0.4 MPa pressure, with the padding rate controlled at 40%~70%. The impregnation and padding operations are repeated once more to complete the two-impregnation and two-padding process. Finally, the nylon fabric that has undergone the two-impregnation and two-padding process is placed in an oven, pre-baked at 80℃ for 3 minutes, and then baked at 150℃ for 1 minute to obtain the ultra-thin UV-resistant nylon fabric.
[0030] Example 2 1. Preparation of titanium dioxide sol Tetrabutyl titanate was added to ethanol, and glacial acetic acid was added to adjust the solution to acidity. The solution was then mechanically stirred until homogeneous to obtain solution a. Deionized water was added to ethanol and stirred until homogeneous to obtain solution b. Solution b was slowly added dropwise to solution a. After the addition was completed, the solution was mechanically stirred for 3.5 hours. After stirring was stopped, the solution was allowed to stand at room temperature (25°C) for 18 hours to obtain a uniformly dispersed titanium dioxide sol.
[0031] The mass ratio of tetrabutyl titanate to ethanol was 1:9; the mass ratio of tetrabutyl titanate to fabric was 1:1; glacial acetic acid was used to adjust the pH of the solution to 4; the stirring rod was used at a speed of 300 r / min for 30 min. The required mass ratio of deionized water to tetrabutyl titanate was 2.5:1, and the mass ratio of ethanol to deionized water was 2:1.
[0032] 2. Preparation of the compound solution for impregnation Titanium dioxide sol and deionized water were mixed at a mass ratio of 1:2 as the base solvent. Hindered amine light stabilizers, UV absorber compositions, dyeing accelerators, inorganic UV stabilizers, and crosslinking agents were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5. The mixture was mechanically stirred for 3.5 hours to obtain a homogeneous and stable impregnation compound solution.
[0033] The composition includes a base solvent with a water bath ratio of 50:1 to the fabric; a hindered amine light stabilizer, UV-660, is used at a dosage of 0.15 parts based on the weight of the nylon fabric; the UV absorber composition consists of 0.50 parts UV-3640, 0.11 parts DHHB, and 0.055 parts 2-(benzo[d]thiazol-2-yl)-4-chlorophenol; a dyeing accelerator, sodium sulfate and micron-sized silica, is used at a dosage of 0.2% based on the weight of the aqueous medium, which is equivalent to 0.06 parts based on the weight of the fabric; an inorganic UV-resistant auxiliary agent, nano-zinc oxide particles (particle size 30±10 nm), is used at a dosage of 0.075 parts based on the weight of the fabric; and a water-soluble end-capped polyurethane crosslinking agent is used at a dosage of 1% based on the weight of the aqueous medium, which is equivalent to 0.30 parts based on the weight of the fabric.
[0034] 3. Prepare the rolling fluid Titanium dioxide sol and deionized water were mixed at a mass ratio of 1:2 as the base solvent. Hindered amine light stabilizers, UV absorber compositions, dyeing accelerators, inorganic UV stabilizers, and crosslinking agents were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5. The mixture was mechanically stirred for 3.5 hours to obtain a homogeneous and stable rolling solution.
[0035] Based on the mass of the aqueous medium: hindered amine light stabilizer UV-660 is 0.03 parts; in the UV absorber composition, UV-3640 is 0.10 parts, DHHB is 0.03 parts, 2-(benzo[d]thiazol-2-yl)-4-chlorophenol is 0.01 parts; dyeing accelerator is 0.02 parts; inorganic UV-resistant auxiliary agent is 0.002 parts; crosslinking agent is 0.01 parts.
[0036] 4. Fabric finishing The nylon fabric was immersed in a compound impregnation solution. The initial water bath temperature was 50℃, and the temperature was increased to 90℃ at a rate of 1.0–1.5℃ / min, and held for 35 minutes. The impregnated fabric was then placed in a padding solution and padded at room temperature and 0.4 MPa pressure, with the padding rate controlled at 40%–70%. The impregnation and padding operations were repeated once more. Finally, the fabric was placed in an oven and pre-baked at 80℃ for 3 minutes, followed by baking at 150℃ for 1 minute to obtain the ultra-thin UV-resistant nylon fabric.
[0037] Example 3 1. Preparation of titanium dioxide sol Tetrabutyl titanate was added to ethanol, and glacial acetic acid was added to adjust the solution to acidity. The solution was then mechanically stirred until homogeneous to obtain solution a. Deionized water was added to ethanol and stirred until homogeneous to obtain solution b. Solution b was slowly added dropwise to solution a. After the addition was completed, the solution was mechanically stirred for 3.5 hours. After stirring was stopped, the solution was allowed to stand at room temperature (25°C) for 18 hours to obtain a uniformly dispersed titanium dioxide sol.
[0038] The mass ratio of tetrabutyl titanate to ethanol was 1:45; the mass ratio of tetrabutyl titanate to fabric was 1:1; glacial acetic acid was used to adjust the pH of the solution to 4; the stirring rod was used at a speed of 300 r / min for 30 min. The required mass ratio of deionized water to tetrabutyl titanate was 2.5:1, and the mass ratio of ethanol to deionized water was 2:1.
[0039] 2. Preparation of the compound solution for impregnation Using the prepared titanium dioxide sol directly as the base solvent, a hindered amine light stabilizer, a UV absorber composition, a dyeing accelerator, an inorganic UV stabilizer, and a crosslinking agent were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5, and the mixture was continuously mechanically stirred for 3.5 hours to obtain a homogeneous and stable impregnation compound solution.
[0040] The ratio of the base solvent to the fabric in the water bath is 50:1; the hindered amine light stabilizer used is UV-660, with a dosage of 0.06 parts based on the weight of the nylon fabric; the UV absorber composition includes 0.20 parts of UV-3640, 0.045 parts of DHHB, and 0.022 parts of 2-(benzo[d]thiazol-2-yl)-4-chlorophenol; the dyeing accelerator uses sodium sulfate and micron-sized silica, with a dosage of 0.12% based on the weight of the aqueous medium, which is equivalent to 0.06 parts based on the weight of the fabric; the inorganic UV-resistant auxiliary agent uses nano-zinc oxide particles (particle size 30±10 nm), with a dosage of 0.075 parts based on the weight of the fabric; and the crosslinking agent uses a water-soluble end-capped polyurethane crosslinking agent, with a dosage of 0.6% based on the weight of the aqueous medium, which is equivalent to 0.30 parts based on the weight of the fabric.
[0041] 3. Prepare the rolling fluid Using the prepared titanium dioxide sol directly as the base solvent, hindered amine light stabilizers, UV absorber compositions, dyeing accelerators, inorganic UV stabilizers, and crosslinking agents were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5, and the mixture was continuously mechanically stirred for 3.5 hours to obtain a homogeneous and stable rolling solution.
[0042] Based on the mass of the aqueous medium: hindered amine light stabilizer UV-660 is 0.03 parts; in the UV absorber composition, UV-3640 is 0.10 parts, DHHB is 0.03 parts, 2-(benzo[d]thiazol-2-yl)-4-chlorophenol is 0.01 parts; dyeing accelerator is 0.02 parts; inorganic UV-resistant auxiliary agent is 0.002 parts; crosslinking agent is 0.01 parts.
[0043] 4. Fabric finishing The nylon fabric was immersed in a compound solution for impregnation. The initial water bath temperature was 50℃, and the temperature was increased to 90℃ at a rate of 1.0–1.5℃ / min, and held for 60 minutes. The impregnated fabric was then placed in a padding solution and padded at room temperature and 0.4 MPa pressure, with the padding rate controlled at 40%–70%. The impregnation and padding operations were repeated once more. Finally, the fabric was placed in an oven and pre-baked at 80℃ for 3 minutes, followed by baking at 150℃ for 1 minute to obtain the ultra-thin UV-resistant nylon fabric.
[0044] Example 4 1. Preparation of titanium dioxide sol Tetrabutyl titanate was added to ethanol, and glacial acetic acid was added to adjust the solution to acidity. The solution was then mechanically stirred until homogeneous to obtain solution a. Deionized water was added to ethanol and stirred until homogeneous to obtain solution b. Solution b was slowly added dropwise to solution a. After the addition was completed, the solution was mechanically stirred for 3.5 hours. After stirring was stopped, the solution was allowed to stand at room temperature (25°C) for 18 hours to obtain a uniformly dispersed titanium dioxide sol.
[0045] The mass ratio of tetrabutyl titanate to ethanol was 1:5; the mass ratio of tetrabutyl titanate to fabric was 1:1; glacial acetic acid was used to adjust the pH of the solution to 4; the stirring rod was used at a speed of 300 r / min for 30 min. The required mass ratio of deionized water to tetrabutyl titanate was 2.5:1, and the mass ratio of ethanol to deionized water was 2:1.
[0046] 2. Preparation of the compound solution for impregnation Titanium dioxide sol and deionized water were mixed at a mass ratio of 1:2 as the base solvent. Hindered amine light stabilizers, UV absorber compositions, dyeing accelerators, inorganic UV stabilizers, and crosslinking agents were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5. The mixture was mechanically stirred for 3.5 hours to obtain a homogeneous and stable impregnation compound solution.
[0047] The ratio of the base solvent to the fabric in the water bath is 30:1; the hindered amine light stabilizer used is UV-660, with a dosage of 0.06 parts based on the weight of the nylon fabric; the UV absorber composition includes 0.20 parts of UV-3640, 0.045 parts of DHHB, and 0.022 parts of 2-(benzo[d]thiazolyl)-4-chlorophenol; the dyeing accelerator uses sodium sulfate and micron-sized silica, with a dosage of 0.2% based on the weight of the aqueous medium, which is equivalent to 0.06 parts based on the weight of the fabric; the inorganic UV-resistant auxiliary agent uses nano-zinc oxide particles (particle size 30±10 nm), with a dosage of 0.075 parts based on the weight of the fabric; and the crosslinking agent uses a water-soluble end-capped polyurethane crosslinking agent, with a dosage of 1% based on the weight of the aqueous medium, which is equivalent to 0.30 parts based on the weight of the fabric.
[0048] 3. Prepare the rolling fluid Titanium dioxide sol and deionized water were mixed at a mass ratio of 1:2 as the base solvent. Hindered amine light stabilizers, UV absorber compositions, dyeing accelerators, inorganic UV stabilizers, and crosslinking agents were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5. The mixture was mechanically stirred for 3.5 hours to obtain a homogeneous and stable rolling solution.
[0049] Based on the mass of the aqueous medium: hindered amine light stabilizer UV-660 is 0.03 parts; in the UV absorber composition, UV-3640 is 0.10 parts, DHHB is 0.03 parts, 2-(benzo[d]thiazol-2-yl)-4-chlorophenol is 0.01 parts; dyeing accelerator is 0.02 parts; inorganic UV-resistant auxiliary agent is 0.002 parts; crosslinking agent is 0.01 parts.
[0050] 4. Fabric finishing The nylon fabric was immersed in a compound impregnation solution. The initial water bath temperature was 50℃, and the temperature was increased to 90℃ at a rate of 1.0–1.5℃ / min, and held for 35 minutes. The impregnated fabric was then placed in a padding solution and padded at room temperature and 0.4 MPa pressure, with the padding rate controlled at 40%–70%. The impregnation and padding operations were repeated once more. Finally, the fabric was placed in an oven and pre-baked at 80℃ for 3 minutes, followed by baking at 150℃ for 1 minute to obtain the ultra-thin UV-resistant nylon fabric.
[0051] Example 5 1. Preparation of titanium dioxide sol Tetrabutyl titanate was added to ethanol, and glacial acetic acid was added to adjust the solution to acidity. The solution was then mechanically stirred until homogeneous to obtain solution a. Deionized water was added to ethanol and stirred until homogeneous to obtain solution b. Solution b was slowly added dropwise to solution a. After the addition was completed, the solution was mechanically stirred for 3.5 hours. After stirring was stopped, the solution was allowed to stand at room temperature (25°C) for 18 hours to obtain a uniformly dispersed titanium dioxide sol.
[0052] The mass ratio of tetrabutyl titanate to ethanol was 1:7.5; the mass ratio of tetrabutyl titanate to fabric was 2:1; glacial acetic acid was used to adjust the pH of the solution to 4; the stirring rod was used at a speed of 300 r / min for 30 min. The required mass ratio of deionized water to tetrabutyl titanate was 2.5:1, and the mass ratio of ethanol to deionized water was 2:1.
[0053] 2. Preparation of the compound solution for impregnation Titanium dioxide sol and deionized water were mixed at a mass ratio of 1:1 as the base solvent. Hindered amine light stabilizers, UV absorber compositions, dyeing accelerators, inorganic UV stabilizers, and crosslinking agents were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5. The mixture was mechanically stirred for 3.5 hours to obtain a homogeneous and stable impregnation compound solution.
[0054] The ratio of the base solvent to the fabric in the water bath is 50:1; the hindered amine light stabilizer used is UV-660, with a dosage of 0.06 parts based on the weight of the nylon fabric; the UV absorber composition includes 0.20 parts of UV-3640, 0.045 parts of DHHB, and 0.022 parts of 2-(benzo[d]thiazol-2-yl)-4-chlorophenol; the dyeing accelerator uses sodium sulfate and micron-sized silica, with a dosage of 0.12% based on the weight of the aqueous medium, which is equivalent to 0.06 parts based on the weight of the fabric; the inorganic UV-resistant auxiliary agent uses nano-zinc oxide particles (particle size 30±10 nm), with a dosage of 0.075 parts based on the weight of the fabric; and the crosslinking agent uses a water-soluble end-capped polyurethane crosslinking agent, with a dosage of 0.6% based on the weight of the aqueous medium, which is equivalent to 0.30 parts based on the weight of the fabric.
[0055] 3. Prepare the rolling fluid Titanium dioxide sol and deionized water were mixed at a mass ratio of 1:1 as the base solvent. Hindered amine light stabilizers, UV absorber compositions, dyeing accelerators, inorganic UV stabilizers, and crosslinking agents were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5. The mixture was mechanically stirred for 3.5 hours to obtain a homogeneous and stable rolling solution.
[0056] Based on the mass of the aqueous medium: hindered amine light stabilizer UV-660 is 0.03 parts; in the UV absorber composition, UV-3640 is 0.10 parts, DHHB is 0.03 parts, 2-(benzo[d]thiazol-2-yl)-4-chlorophenol is 0.01 parts; dyeing accelerator is 0.02 parts; inorganic UV-resistant auxiliary agent is 0.002 parts; crosslinking agent is 0.01 parts.
[0057] 4. Fabric finishing The nylon fabric was immersed in a compound impregnation solution. The initial water bath temperature was 50℃, and the temperature was increased to 90℃ at a rate of 1.0–1.5℃ / min, and held for 35 minutes. The impregnated fabric was then placed in a padding solution and padded at room temperature and 0.4 MPa pressure, with the padding rate controlled at 40%–70%. The impregnation and padding operations were repeated once more. Finally, the fabric was placed in an oven and pre-baked at 80℃ for 3 minutes, followed by baking at 150℃ for 1 minute to obtain the ultra-thin UV-resistant nylon fabric.
[0058] Example 6 1. Preparation of titanium dioxide sol Tetrabutyl titanate was added to ethanol, and glacial acetic acid was added to adjust the solution to acidity. The solution was then mechanically stirred until homogeneous to obtain solution a. Deionized water was added to ethanol and stirred until homogeneous to obtain solution b. Solution b was slowly added dropwise to solution a. After the addition was completed, the solution was mechanically stirred for 3.5 hours. After stirring was stopped, the solution was allowed to stand at room temperature (25°C) for 18 hours to obtain a uniformly dispersed titanium dioxide sol.
[0059] The mass ratio of tetrabutyl titanate to ethanol was 1:15; the mass ratio of tetrabutyl titanate to fabric was 1:1; glacial acetic acid was used to adjust the pH of the solution to 4; the stirring rod was used at a speed of 300 r / min for 30 min. The required mass ratio of deionized water to tetrabutyl titanate was 2.5:1, and the mass ratio of ethanol to deionized water was 2:1.
[0060] 2. Preparation of the compound solution for impregnation Titanium dioxide sol and deionized water were mixed at a mass ratio of 1:3 as the base solvent. Hindered amine light stabilizers, UV absorber compositions, dyeing accelerators, inorganic UV stabilizers, and crosslinking agents were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5. The mixture was mechanically stirred continuously for 3.5 hours to obtain a homogeneous and stable impregnation compound solution.
[0061] The base solvent and the water bath ratio of the fabric are 60:1; the hindered amine light stabilizer is UV-660, with a dosage of 0.06 parts based on the weight of the nylon fabric; the UV absorber composition includes 0.20 parts of UV-3640, 0.045 parts of DHHB, and 0.022 parts of 2-(benzo[d]thiazol-2-yl)-4-chlorophenol; the dyeing accelerator is sodium sulfate and micron-sized silica, with a dosage of 0.1% based on the weight of the aqueous medium, which is equivalent to 0.06 parts based on the weight of the fabric; the inorganic UV-resistant auxiliary agent is nano-zinc oxide particles (particle size 30±10 nm), with a dosage of 0.075 parts based on the weight of the fabric; the crosslinking agent is a water-soluble end-capped polyurethane crosslinking agent, with a dosage of 0.5% based on the weight of the aqueous medium, which is equivalent to 0.30 parts based on the weight of the fabric.
[0062] 3. Prepare the rolling fluid Titanium dioxide sol and deionized water were mixed at a mass ratio of 1:3 as the base solvent. Hindered amine light stabilizers, UV absorber compositions, dyeing accelerators, inorganic UV stabilizers, and crosslinking agents were added to the base solvent. Glacial acetic acid was added to adjust the pH of the system to 5. The mixture was mechanically stirred for 3.5 hours to obtain a homogeneous and stable rolling solution.
[0063] Based on the mass of the aqueous medium: hindered amine light stabilizer UV-660 is 0.03 parts; in the UV absorber composition, UV-3640 is 0.10 parts, DHHB is 0.03 parts, 2-(benzo[d]thiazol-2-yl)-4-chlorophenol is 0.01 parts; dyeing accelerator is 0.02 parts; inorganic UV-resistant auxiliary agent is 0.002 parts; crosslinking agent is 0.01 parts.
[0064] 4. Fabric finishing The nylon fabric was immersed in a compound solution for impregnation. The initial water bath temperature was 50℃, and the temperature was increased to 90℃ at a rate of 1.0–1.5℃ / min, and held for 35 minutes. The impregnated fabric was then placed in a padding solution and padded at room temperature and 0.4 MPa pressure, with the padding rate controlled at 40%–70%. The impregnation and padding operations were repeated once more. Finally, the fabric was placed in an oven and pre-baked at 80℃ for 3 minutes, followed by baking at 130℃ for 1 minute to obtain the ultra-thin UV-resistant nylon fabric.
[0065] Performance testing 1. Ultraviolet transmittance test The ultraviolet transmittance of the fabric samples in each embodiment was tested using a Shimadzu UV-3600i Plus UV-Vis-NIR spectrophotometer, and the results are as follows: Figure 1 As shown.
[0066] Example 1 has the lowest ultraviolet transmittance, with the highest being at 400 nm. Its ultraviolet transmittance is also less than 2%, and the average transmittance in UVA and UVB is 0.29% and 0.19%, respectively, showing excellent ultraviolet protection capabilities.
[0067] The results of comparing Example 1 with the untreated raw fabric are as follows: Figure 2 As shown, the ultraviolet transmittance of Example 1 after treatment by the present invention is much lower than that of the original fabric.
[0068] Example 1 was sent to Hangzhou Yanqu Information Technology Co., Ltd. (equipment: UV transmittance tester, Shaoxing Libixin LBX-902A) to test the UPF value. The test results are as follows. Figure 3 As shown, the UPF value of Example 1 is greater than 2900, which far exceeds the standard requirement of 50+ UPF value for UV-protective fabrics, demonstrating the excellent UV protection capability of the present invention.
[0069] 2. Water wash resistance test Referring to GB / T 8629-2017 "Test Procedures for Textiles - Household Washing and Drying", the machine washing conditions were a Type A standard washing machine, washing program 3G, and ECE type standard detergent 98 (phosphate-free). The ultraviolet transmittance of the test samples was measured after 5 and 10 standard washes, and the results are shown in Table 1.
[0070] Table 1. UV transmittance after 5 and 10 standard washes. As shown in Table 1, after 10 standard washes, the ultraviolet transmittance of all six samples in the UVA and UVB bands was less than 5%, with Example 1 showing the best performance, with ultraviolet transmittance of 0.82% and 0.20% in the UVA and UVB bands, respectively. The results indicate that nylon fabrics treated by the method of this invention have excellent wash resistance.
Claims
1. A method for UV-resistant finishing of ultra-thin nylon fabrics, characterized in that, include: Titanium dioxide sol, hindered amine light stabilizer, UV absorber composition, dyeing accelerator, inorganic UV stabilizer and crosslinking agent are dispersed in an aqueous medium and the pH is adjusted to 4-6 to prepare a homogeneous finishing working solution. The weight is 50±2 g / m 2 The nylon fabric is placed into the finishing working solution for continuous padding finishing, the continuous padding finishing including at least one immersion and at least one rolling, the roll-off rate is controlled to be 40% to 70%, so that the finishing working solution is evenly loaded on the surface and inside of the fabric fibers. The fabric loaded with finishing solution was pre-baked and then baked at high temperature to obtain an ultra-thin UV-resistant nylon fabric. The ultraviolet absorber composition comprises the commercially available compound ultraviolet absorber UV-3640, hexyl diethylaminohydroxybenzoylbenzoate, and 2-(benzo[d]thiazol-2-yl)-4-chlorophenol.
2. The method for UV-resistant finishing of ultra-thin nylon fabric according to claim 1, characterized in that, The continuous impregnation finishing process is a two-impregnation and two-rolling process, which includes: performing one impregnation and one rolling in sequence, and then repeating one impregnation and one rolling.
3. The method for UV-resistant finishing of ultra-thin nylon fabric according to claim 1, characterized in that, The ultraviolet absorber composition, based on the weight of the nylon fabric, comprises the following components by mass: 0.2-0.5 parts of commercially available compound ultraviolet absorber UV-3640, 0.05-0.15 parts of diethylaminohydroxybenzoylhexyl benzoate, and 0.02-0.06 parts of 2-(benzo[d]thiazolyl)-4-chlorophenol.
4. The method for UV-resistant finishing of ultra-thin nylon fabric according to claim 1, characterized in that, The finishing working solution includes a compound solution for impregnation and a rolling solution; The compound solution for impregnation, based on the weight of the nylon fabric, comprises the following components by mass: hindered amine light stabilizer 0.02–0.2 parts, UV absorber composition 0.25–0.70 parts, aqueous medium 30–60 parts, dyeing accelerator 0.05–0.15 parts, inorganic UV-resistant auxiliary agent 0.04–0.2 parts, and crosslinking agent 0.3–0.6 parts. In the rolling solution, based on the mass of the aqueous medium, the mass parts of each component are as follows: 0.03 parts hindered amine light stabilizer, 0.14 parts ultraviolet absorber composition, 0.02 parts dyeing accelerator, 0.002 parts inorganic anti-ultraviolet auxiliary agent, and 0.01 parts crosslinking agent.
5. The method for UV-resistant finishing of ultra-thin nylon fabric according to claim 1, characterized in that, The preparation method of the titanium dioxide sol includes: mixing tetrabutyl titanate and ethanol, adding glacial acetic acid to adjust the pH to 4-5, stirring, and then adding a mixture of deionized water and ethanol dropwise, stirring continuously for 3-4 h, and then allowing it to stand and age at 25-35℃ for 12-24 h to obtain the titanium dioxide sol; wherein the mass ratio of tetrabutyl titanate to ethanol is 1:5-55, and the mass ratio of tetrabutyl titanate to deionized water is 1:2-3.
6. The method for UV-resistant finishing of ultra-thin nylon fabric according to claim 1, characterized in that, The aqueous medium of the finishing working solution is a mixture of titanium dioxide sol and deionized water, and the mass ratio of titanium dioxide sol to deionized water is 1:1 to 4; the hindered amine light stabilizer is UV-660 or UV-770; the crosslinking agent is a capped polyurethane crosslinking agent or a multifunctional aziridine crosslinking agent.
7. The method for UV-resistant finishing of ultra-thin nylon fabric according to claim 1, characterized in that, During the impregnation process, the finishing working solution is heated to 50-55°C and then added to the nylon fabric. The temperature is increased to 85-95°C at a rate of 1.0-1.5°C / min and held for 30-70 min. The rolling treatment is carried out at room temperature.
8. The method for UV-resistant finishing of ultra-thin nylon fabric according to claim 1, characterized in that, The pre-baking temperature is 70–100℃, and the pre-baking time is 2–5 min; the high-temperature baking temperature is 120–160℃, and the baking time is 1–2 min.
9. The method for UV-resistant finishing of ultra-thin nylon fabric according to claim 1, characterized in that, The ultra-thin UV-resistant nylon fabric has a UPF value ≥ 2900, and the average UVA transmittance and average UVB transmittance are both less than 3%.
10. An ultra-thin UV-resistant nylon fabric prepared by the method according to any one of claims 1 to 9, characterized in that, After 10 standard household washes, the fabric showed an average UVA transmittance and an average UVB transmittance of less than 5%.